A comprehensive search for mutations in the PKD1 and PKD2 in Japanese subjects with autosomal dominant polycystic kidney disease. (3rd April 2014) - Kurashige, M.; Hanaoka, K.; Imamura, M.; Udagawa, T.; Kawaguchi, Y.; Hasegawa, T.; Hosoya, T.; Yokoo, T.; Maeda, S.
<x xml:space="preserve">Abstract</x> To elucidate the genotypic and phenotypic characteristics of autosomal dominant polycystic kidney disease (ADPKD) in Japanese populations, we performed a comprehensive search for mutations in PKD1 and PKD2 in 180 Japanese ADPKD patients from 161 unrelated families. We identified 112 (89 PKD1 and 23 PKD2) mutations within 135 families. Patients with PKD2 mutations account for 23.6% of all Japanese ADPKD families in this study. Seventy‐five out of the 112 mutations have not been reported previously. The estimated glomerular filtration rate (eGFR) decline was significantly faster in patients with PKD1 mutations than in those with PKD2 mutations (−3.25 and −2.08 ml min−1 year−1 for PKD1 and PKD2, respectively, p < 0.01). These results indicate that mutations within PKD1 and PKD2 can be linked to most of the cases of Japanese ADPKD, and the renal function decline was faster in patients with PKD1 mutations than in those with PKD2 mutations also in the Japanese ADPKD. We also found that PKD2 mutations were more frequent in Japanese ADPKD than that in European or American ADPKD.